2018
DOI: 10.1590/2179-8087.150285
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Constituents Isolated from the Stem Bark of Bauhinia monandra

Abstract: The methanolic extract from stem bark of Bauhinia monandra, a medicinal plant employed in folk medicine, yielded by column chromatography lup-20(29)-en-3β,24-diol (1) and methyl galloate (2) along with β-sitosterol (3). These known phytoconstituents are being reported for the first time from this plant and their structures were established by NMR and MS spectral studies and by comparison with their literature data. Furthermore, lup-20(29)-en-3β,24-diol (1), a minor constituent, was isolated from this genus for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Overall, the AcOEt extracts show a better reduction profile. And their richness in electron donating phytophenols and flavonoids are responsible for this (Argolo et al, 2004;Aderogba et al, 2006;Kumaran and Karunakaran, 2007;Alade et al, 2011;Ferrari et al, 2019). The reducing activity by NO inhibition and FRAP assay of B. strychnifolia leaf and stem extracts has been shown (Itharat et al, 2016;Praparatana et al, 2022).…”
Section: Antioxidant Profile By the Dpph Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the AcOEt extracts show a better reduction profile. And their richness in electron donating phytophenols and flavonoids are responsible for this (Argolo et al, 2004;Aderogba et al, 2006;Kumaran and Karunakaran, 2007;Alade et al, 2011;Ferrari et al, 2019). The reducing activity by NO inhibition and FRAP assay of B. strychnifolia leaf and stem extracts has been shown (Itharat et al, 2016;Praparatana et al, 2022).…”
Section: Antioxidant Profile By the Dpph Methodsmentioning
confidence: 99%
“…Nevertheless, its values are lower than that of ascorbic acid (429407.783 ± 586.14 µg EFeSO 4 /g ES) taken as reference antioxidant.Overall, the AcOEt extracts show a better reduction profile. And their richness in electron donating phytophenols and flavonoids are responsible for this(Argolo et al, 2004;Aderogba et al, 2006;Kumaran and Karunakaran, 2007;Alade et al, 2011;Ferrari et al, 2019).…”
mentioning
confidence: 99%
“…A mixture of this native species and other Bauhinia species are generally applied for the treatment of ailments besides diabetes (Holdsworth 1990;Da Silva et al 2000;Mendes et al 2006;Dapar et al 2020b). 29)-en-3β,24-diol, was isolated from the genus Bauhinia for the first time (Ferrari et al 2019). Many studies have revealed numerous pharmacological activities from different Bauhinia (Holdsworth 1990;Da Silva et al 2000), including the antioxidant potential of B. monandra (Nworie and Okorie 2018).…”
mentioning
confidence: 99%